2014
DOI: 10.1111/ger.12144
|View full text |Cite
|
Sign up to set email alerts
|

Dentition, nutritional status and adequacy of dietary intake among older residents in assisted living facilities

Abstract: Malnutrition and inadequate protein intake were very common and associated with dentition among older people with multiple disabilities in assisted living facilities. Assessment of dental status should be part of good nutritional care in long-term care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 51 publications
4
58
1
1
Order By: Relevance
“…Thus, understanding both dental status and dysphagia risk may be helpful in devising strategies intended to prevent malnutrition. In contrast to previous studies [52, 53], no significant association between dental status and malnutrition risk status was observed in the current study. However, as expected, we observed that with increasing risk of dysphagia (increasing EAT-10 scores), the prevalence ratio of malnutrition risk also increased.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, understanding both dental status and dysphagia risk may be helpful in devising strategies intended to prevent malnutrition. In contrast to previous studies [52, 53], no significant association between dental status and malnutrition risk status was observed in the current study. However, as expected, we observed that with increasing risk of dysphagia (increasing EAT-10 scores), the prevalence ratio of malnutrition risk also increased.…”
Section: Discussioncontrasting
confidence: 99%
“…Another cross-sectional study in 197 community-dwelling elderly individuals showed that the reduction in perioral muscle strength due to sarcopenia results in reduced jaw opening force and tongue pressure [ 7 ]. The reduction in masseter muscle thickness (MMT) has also been shown to be related to a reduction in occlusal force and chewing ability [ 8 ], leading to difficulties in eating [ 9 ], and consequently, risk of malnutrition [ 10 ]. A previous study showed that 25% of community-dwelling elderly individuals were at risk of malnutrition [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weakening of oral muscles with aging might diminish swallowing and chewing ability and thus reduce adequate nutrition. In addition, loss of teeth, ill-fitted dentures, and dry mouth further diminishes the initial step of digestion, which starts in the mouth and requires adequate masticatory ability to form bolus of food prior to swallowing [26]. A recent study by Hiramatsu et al [27] compared swallowing and chewing ability in a group of healthy older adults (OAs, n = 23, age∼76 y) with a group of younger healthy adults (YAs, n = 23, age∼29 y).…”
Section: Impaired Digestion In Older Adults Impacts Nutrients Intake mentioning
confidence: 99%